Kesehatan Reproduksi pada Remaja Perempuan di Desa Tosora Kecamatan Majauleng Kabupaten Wajo - Tetti Surianti; Lisna Lisna (Journal Research of Nursing & Midwifery (JRNM), 2025)
Adolescent girls are a highly vulnerable group to reproductive health problems, particularly those related to menstruation. In rural areas such as Tosora Village, Majauleng Subdistrict, discussions about reproductive health are still considered taboo, contributing to the low level of knowledge among adolescent girls. This study aimed to analyze the level of knowledge, attitudes, menstrual hygiene practices, and sources of reproductive health information among adolescent girls. The study employed a descriptive quantitative design with a cross-sectional approach involving 54 adolescent girls aged 13–19 years selected through purposive sampling. Data were collected using a structured questionnaire and analyzed descriptively. The results showed that the majority of respondents had low knowledge of reproductive health (61.1%) and poor menstrual hygiene practices (55.6%). As many as 48.1% of adolescents obtained information from peers and 37.0% from social media, while only 9.3% received information from parents. It is concluded that the knowledge and reproductive health practices of adolescent girls in Tosora Village remain low, influenced by limited family communication and inadequate formal education, indicating the need for school- and family-based educational interventions.